Minerals-concentrators of rare-earth elements in basites-ultrabasites intrusives of Norilsk district - Yu. D. Gritsenko; A. A. Serova (Известия высших учебных заведений: Геология и разведка)
The conditions of being, the history of formation and transformation of minerals-concentrators of rare-earth elements (REE) - apatite minerals group and epidote minerals group, have been studied and described. Allanite has been determined to be mostly developed in the halos of the fluid action a solid contact of sulfide ores containing rich pneu matolytic mineralization of the platinum-group elements (PGM) and gold. Apatite and allanite are found among sulfides and in rims of the fluid action over the drops of sulphides in the horizon of the disseminated ores. The composition of Apatite-I has evolved from a OH-containing chlorapatite to chlorapatite containing up to 2,3 wt. % of lanthanides; Apatite-II - from OH-Cl-bearing fluorapatite to fluorapatite. The lanthanides reieased during replacement of chlorapatite-I by fluorapatite-II, probably entering the composition of the produced pneumatoiytic alianite-(Ce). In the areas of mineral ores with imposed metamorphism, the pneumatoiytic apatite partially or totally is substituted by hydroxyapatite-III, allanite - by water-containing allanite with the content of the epidote and clinozoisite minals - 30-35 mol. %. The spectra of REE distribution in apatite have been determined to reflect more accurately their ratios in rocks, the spectra of REE distribution for allanite are characterized by a steeper slope from lighter to heavier lanthanides. The ratio of La, Ce and Nd in chlorapatite corresponds to the distribution of these elements as in the host picrite horizon, as well in the rocks of the intrusives as a whole. Allanite, in return, is more enriched in cerium and lanthanum and depleted in neodymium.